2020
DOI: 10.1002/adfm.201909673
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Semiconducting Polymer Dots with Rapid Clearance for Second Near‐Infrared Photoacoustic Imaging and Photothermal Cancer Therapy

Abstract: Phototheranostic agents in the second near‐infrared (NIR‐II) window (1000–1700 nm) are emerging as a promising theranostic platform for precision medicine due to enhanced penetration depth and minimized tissue exposure. The development of metabolizable NIR‐II nanoagents for imaging‐guided therapy are essential for noninvasive disease diagnosis and precise ablation of tumors. Herein, metabolizable highly absorbing NIR‐II conjugated polymer dots (Pdots) are reported for the first time for photoacoustic imaging g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 41 publications
0
93
0
Order By: Relevance
“…e) Calculation of the photothermal conversion efficiency at 1064 nm. f) Comparison of photothermal conversion efficiency (η) of reported PTT agents in the NIR‐II biowindow: 1) AuNCs@SiO 2 ; 2) Au 3 Cu@PEG TPNCs; [ 46 ] 3) Au‐wires‐on‐AuNR; [ 47 ] 4) Pt Spiral; [ 48 ] 5) Cu 2 MnS 2 NPs; [ 49 ] 6) Nb 2 C (Mxene); [ 50 ] 7) Cu 3 BiS 3 NRs; [ 51 ] 8) L‐Pdots; [ 52 ] 9) TBDOPV‐DT NPs; [ 53 ] 10) SPN‐DT. [ 54 ] g) Relative viabilities of 4T1 cells after co‐incubation with different concentrations of AuNCs@SiO 2 under different 1064 nm laser treatment (0.5 W cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…e) Calculation of the photothermal conversion efficiency at 1064 nm. f) Comparison of photothermal conversion efficiency (η) of reported PTT agents in the NIR‐II biowindow: 1) AuNCs@SiO 2 ; 2) Au 3 Cu@PEG TPNCs; [ 46 ] 3) Au‐wires‐on‐AuNR; [ 47 ] 4) Pt Spiral; [ 48 ] 5) Cu 2 MnS 2 NPs; [ 49 ] 6) Nb 2 C (Mxene); [ 50 ] 7) Cu 3 BiS 3 NRs; [ 51 ] 8) L‐Pdots; [ 52 ] 9) TBDOPV‐DT NPs; [ 53 ] 10) SPN‐DT. [ 54 ] g) Relative viabilities of 4T1 cells after co‐incubation with different concentrations of AuNCs@SiO 2 under different 1064 nm laser treatment (0.5 W cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The blood routine indexes including white blood cells, red blood cells, hemoglobin, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and mean platelet volume of SPN‐treated mice are not significantly different than that observed in control mice, suggesting the biosafety of SPNs in mice. [ 61 ] However, long‐term (longer than 14 days) safety studies have not been reported, which is important for clinical applications of promising SPNs. The development of SPNs with renal clearance or biodegradation capability is an option to accelerate the clearance of SPNs from the body.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this issue, Yuan and co‐workers fabricated an ultrasmall SPN (SPN37‐S) based on a novel SP (SP37), Poly([2,5‐bis(2‐decyltetradecyl)‐2,5‐dihydropyrrolo[3,4‐c]pyrrole‐1,4‐dione‐3,6‐dithienyl]‐ co ‐[6‐(2‐ethylhexyl)‐[1,2,5]thiadiazolo[3,4‐f]benzotriazole‐4,8‐diyl]), to compare the tumor accumulation ability with large SPN (SPN37‐L). [ 61 ] SPN37‐L was obtained via a normal nanoprecipitation method with the assistance of poly(styrene‐ co ‐maleic anhydride) (PSMA). A modified nanoprecipitation method was fabricated to obtain SPN37‐S.…”
Section: Nir‐ii Photothermal Therapymentioning
confidence: 99%
“…In addition, OSPs-or OSOs-based OSNs have excellent light-capturing capability, strong photostability, good biocompatibility, and design flexibility, which make them good candidates for NIR-II PAI-guided PTT. To date, OSPs that have strong NIR-II absorption profile are mainly focused on BBT-, thiadiazolobenzotriazole-, thiadiazoloquinoxaline-, and thiophene-fused benzodifurandione-based oligo (pphenylenevinylene)-based skeleton structures, 43,[64][65][66] and their in vivo phototheranostics were widely investigated. Fan et al designed a series of semiconducting polymer nanoparticles (SPNs) with absorption beyond 1000 nm for efficient PAI-guided PTT in the NIR-II window.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…To address this issue, Yuan's group reported a metabolizable semiconducting polymer dots (Pdots) for NIR-II phototheranostic. 66 In this study, ultrasmall Pdots (S-Pdots) with average diameter of 4 nm were fabricated via a modified nanoprecipitation method. The as-prepared Pdots showed excellent photothermal performance with a high PCE of 53.1%, guarantying their anticancer capability.…”
Section: Photothermal Therapymentioning
confidence: 99%